Wrist rotations about one or two axes affect maximum wrist strength. (March 2016) - Plewa, Katherine; Potvin, Jim R.; Dickey, James P.
Abstract: Most wrist strength studies evaluate strength about one axis, and postural deviations about that same axis. The purpose of this study was to determine if wrist posture deviations about one axis (e.g. flexion/extension), or two axes (e.g. flexion/extension and pronation/supination), affect the strength about another axis (e.g. ulnar deviation). A custom-built instrumented handle was used to measure maximum static isometric torque exertions at 18 wrist postures (combinations of flexion/extension, radial/ulnar deviation, and pronation/supination). Ulnar deviation torques were highest when the wrist was in neutral. This pattern was not maintained for the other torque directions; the generated torque tended to be highest when the wrist posture was not neutral. The effects were similar for male and female subjects, although male subjects exerted significantly larger torques in all directions. This study illustrates that there is a complex relationship between wrist posture and maximal wrist torques. Graphical abstract: Maximum wrist torques in flexion/extension and radial/ulnar deviation were measured in complex wrist/forearm positions. Maximum torque was significantly greater in male subjects than females, and varied significantly between wrist postures. Highlights: Maximum wrist torques in flexion/extension and radial/ulnar deviation were measured. Wrists were neutral or deviated about 1 axis or 2 axes (e.g. flexion and pronation). Maximum torque was significantly greater in male subjects compared to females. Maximum torque was significantly higher when the wrist was deviated away from neutral. These maximum torques and trends should be incorporated into ergonomic software.